FAKTOR-FAKTOR YANG MEMPENGARUHI CASH HOLDING PADA PERUSAHAAN MANUFAKTUR - Meliana Angela Lintungan; Lukman Surjadi (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this study is to examine and obtain empirical evidence of the effect of profitability, leverage, firm size and growth opportunity on cash holding in manufacturing companies listed on the Indonesia Stock Exchange during 2018-2020. This study used secondary data in the form of company financial statements. The sample selection in this study used purposive sampling method based on certain criteria which were processed using the Eviews 12.0 program. The amount of data obtained is 240 data for 3 years. The results of this study indicate that profitability and firm size has a significant positive effect on cash holding, growth opportunity has a significant negative effect on cash holding, while leverage have no significant effect on cash holding.